An Evaluation of Family-Based Treatment for OCD in Japan: A Pilot Randomized Controlled Trial - Kobayashi, Yuki; Kanie, Ayako; Nakagawa, Atsuo; Takebayashi, Yoshitake; Shinmei, Issei; Nakayama, Noriko; Yamaguchi, Keiko; Nakayama, Chiaki; Hirabayashi, Naotsugu; Mimura, Masaru; Horikoshi, Masaru (Frontiers in Psychiatry, 2020)
Objective: Although family involvement in the treatment of obsessive-compulsive disorder (OCD) produces a reduction in OCD symptoms and has significant effects on global functioning, few studies have focused on family intervention as part of OCD treatment in Japan. This study aims to examine the feasibility and efficacy of the family-based exposure and response prevention program (FERP) for adult patients with OCD and their family members. Design: Randomized controlled pilot study. Methods: A total of 18 outpatients aged 18–65 years with a primary diagnosis of OCD and one family member of each patient were randomized to an intervention group or a control group (1:1). The intervention group received the family-based ERP program (FERP), which consisted of 16 weekly face-to face CBT sessions, including eight joint sessions with family members, in addition to treatment-as-usual (TAU). The control group received TAU alone. The primary outcome was the alleviation of OCD symptoms, as measured by changes in the total Y-BOCS score from baseline to posttreatment. Analyses were provided on an intention-to-treat basis, and linear mixed models were used to test for significant group differences. Results: After 16 weeks, patients allocated to the FERP program showed improvement in OCD symptom severity, as measured by the total change score of the Yale-Brown Obsessive-Compulsive Scale (Hedges’ g = -1.58), as compared to the control group. Two patients (22.2%) in the FERP group reached remission, and five patients (55.6%) in the FERP group achieved treatment response. Clinical global improvement measured by the FAS-SR scores, K6 scores, and CGI-S scores was also observed (Hedges’ g = -1.35, -1.25, -1.26, respectively) in the FERP group, as compared to the control group. The dropout rate from the study was low (n=2, 11.8%) and no adverse events were reported in the FERP group. Conclusion: Our results suggest that FERP may be an effective program for reducing patients’ OCD symptoms. Clinical Trial Registration: University Hospital Medical Information Network Clinical Trials Registry: UMIN000021763